The omission of routine preoperative midazolam prescription is associated with increased preoperative sympathetic activation but not mortality: a propensity score matched, before-and-after study - Carolin Jung; Andre Gerdes; Hans-Joerg Gillmann; Thomas Stueber (Perioperative Medicine)
Abstract Background Guidelines recommend avoiding preoperative anxiolytic medication with midazolam. However, the risk–benefit ratio of preoperative midazolam prescriptions remains unclear. This study aimed to investigate the association between preoperative midazolam prescription and perioperative in-house mortality as well as preoperative cardiovascular stress. Methods We performed a retrospective single-center propensity score-matched study in a university hospital in Germany before and after de-implementation of routine oral preoperative midazolam prescription in December 2018. We included adult patients who underwent general anesthesia between December 1, 2017, and November 31, 2019. Patients who received midazolam premedication before de-implementation were compared to those who did not receive midazolam after de-implementation. After propensity score matching, we estimated the treatment effects using regression modeling. The primary endpoint was inhospital mortality after general surgery. Secondary endpoints included pre-induction vital signs, duration of stay in the postanesthesia care unit, and medications administered. Results After propensity score matching, we analyzed 7421 patients in each group. In this adjusted analysis, premedication with midazolam was not associated with mortality (OR 0.91, 95% CI 0.60 to 1.38, p = 0.662). Midazolam premedication was associated with significantly lower pre-induction blood pressures, with an estimated average treatment effect for systolic blood pressure of − 5.33 mmHg (SE 0.41, 95% CI − 6.13 to − 4.52 mmHg). Conclusions Midazolam prescription was not associated with increased mortality in a large cohort of surgical patients but with a lower pre-induction blood pressure and heart rate, suggesting a potential reduction in cardiovascular stress.